Evaluation of critical value and urgent sample notification at clinical biochemistry laboratory in a tertiary care hospital - Menezes, Geraldine; Peter, Stella S.; Shanthaveeranna, Girish K. (International Journal of Research in Medical Sciences, 2022)
Background: Critical value and urgent sample result notification is widely accepted in the diagnostic fraternity as an important factor, as it may affect patient care and safety. Timely release and notification of these test result as per the individual laboratory protocol becomes an internal part of quality reporting system. The present study was aimed at evaluating the effective implementation of the existing protocol of urgent clinical notification (UCN) in the clinical biochemistry laboratory of tertiary care hospital and evaluating the turnaround time for urgent samples and critical results listed under UCN protocol in the clinical biochemistry laboratory. Methods: A prospective, observational study was conducted in clinical biochemistry laboratory of a tertiary care hospital. Descriptive statistics was calculated for all the data by Mann-Whitney and Wilcoxon test. Results: Majority of the critical results were informed to the clinical personnel by the clinical laboratory. Out of 4687 critical results, 25.41% critical results were informed directly to the ward through telephonic communication. Documentation of critical values in the dedicated register and lab information system (LIS) was 25.41% and 40.28% respectively. 421 (9%) out of 4687 critical results were not notified. The median turnaround time for all urgent tests and critical results was found to be 72.33 minutes and 76.00 minutes respectively. Conclusions: This study highlighted various approaches to improve the critical value notification and its turnaround time and status of UCN in laboratory